Quercetin and its Natural Sources in Wound Healing Management - Polerà, Nicoletta; Badolato, Mariateresa; Perri, Filomena; Carullo, Gabriele; Aiello, Francesca (Current Medicinal Chemistry, 2019)
Giving a glance to the report of Wound Care Market by Product updated in 2017, we can see that wound care market is expected to reach USD 22.01 billion by 2022 from USD 18.35 billion at a CAGR of 3.7%. Numerous factors are driving the growth of this market, including the increasing prevalence of chronic wounds and acute wounds, increasing aged population, rising R activities and advancement in the field of wound care research. Advanced wound management products are accounted for the largest market share in 2017. These evidences mean that the wound care research represents a Clinical Emergency other than an interesting Marketing tool. Drug therapies so far fight efficaciously with the opportunistic pathologies derived from chronic wounds, although an unsolved challenge is still finding a useful remedy to correct the impaired wound healing process and overcome the chronic wound state, to avoid bacterial rising and severe pain. Traditional medicinal plants have been widely used in the management of wounds and different plant extracts have been evaluated for their wound healing properties through both in vitro and in vivo studies. Their phytochemical components in particular quercetin, contribute to their remedial properties in wound repair. Quercetin has important biological activities related to the improvement of the wound healing process. The present review discusses and focuses on the latest findings of the wound healing properties of quercetin, alone or as a part of plant extract, and its role as a new frontier in wound repair.
Keywords: quercetin loaded vehicles